전폐절제술후 발생한 합병증에 대한 분석 - 허강배 (Taehan Hyungbu Oekwa Hakhoe chi, 1993)
As developing surgical techniques and postoperative cares, a pneumonectomy is a relatively popular surgical method in disease which is not treated completely with other type of pulmonary resection, but a postpneumonectomy complication is a life-threatening serious problem if it occurred. We performed one hundred twenty-five cases of pneumonectomy for treatment of various causes of pulmonary diseases in Kosin Medical College during about ten years, and we experienced 41 cases of postoperative complications in 29 patients, so we analyzed them. The most common complication is an empyema thoracis in 13 cases[10.4%], of which one case combined with bronchopleural fistula died on early postoperative day. Of them except one case, the early postoperative empyema thoracis[within 30 days] were 6 cases, and the late postoperative empyema thoracis[above 30 days] were 6 cases. The main etiologic pathogens were a staphylococcus in early postoperative empyema and a streptococcus in late postoperative empyema, but the most cases were mixed infections with pseudomonas, klebsiella, acinectobacter, and candida. The treatment of postoperative empyema thoracis were that 4 cases were treated with open drainage using chest tube, 7 cases with Clagett`s operation, and 1 case with thoracoplasty. The next common complication was a postoperative serious respiratory insufficiency in 7 cases. And the other complications were massive postoperative bleeding in 5 cases, of which 2 cases advanced to occurrence of postoperative empyema thoracis, and wound disruption in 4 cases, cardiac arrhythmia in 3 cases, contralateral pneumothorax and pneumonia in each of 2 cases, esophagopleural fistula in 1 case. The postoperative deaths were 9 cases[7.2%] of 125 cases, the causes of death were respiratory insufficiency in 6 cases, sepsis in 2 cases, and cardiac arrhythmia in 1 case.